2018
DOI: 10.1016/j.physbeh.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic and non-homeostatic appetite control along the spectrum of physical activity levels: An updated perspective

Abstract: The current obesogenic environment promotes physical inactivity and food consumption in excess of energy requirements, two important modifiable risk factors influencing energy balance. Habitual physical activity has been shown to impact not only energy expenditure, but also energy intake through mechanisms of appetite control. This review summarizes recent theory and evidence underpinning the role of physical activity in the homeostatic and non-homeostatic mechanisms controlling appetite. Energy intake along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 110 publications
2
76
0
1
Order By: Relevance
“…In line with previous findings , participants with lower habitual MVPA levels showed higher tendencies for disinhibition and binge eating at baseline, factors that may have influenced the greater increases in EI and subsequent greater weight compensation in response to the exercise intervention. This assumption is supported by previous findings showing that individuals with lower levels of measured MVPA have weaker appetite control and satiety response to food and thus have an impaired regulation of energy balance compared with their more active counterparts . Consequently, in our study, participants with lower levels of habitual MVPA and/or PAEE at baseline may have had a more impaired regulation of energy balance than those with higher levels of habitual MVPA and/or PAEE, and this became particularly apparent with the onset of the exercise intervention.…”
Section: Discussionsupporting
confidence: 88%
“…In line with previous findings , participants with lower habitual MVPA levels showed higher tendencies for disinhibition and binge eating at baseline, factors that may have influenced the greater increases in EI and subsequent greater weight compensation in response to the exercise intervention. This assumption is supported by previous findings showing that individuals with lower levels of measured MVPA have weaker appetite control and satiety response to food and thus have an impaired regulation of energy balance compared with their more active counterparts . Consequently, in our study, participants with lower levels of habitual MVPA and/or PAEE at baseline may have had a more impaired regulation of energy balance than those with higher levels of habitual MVPA and/or PAEE, and this became particularly apparent with the onset of the exercise intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely research in cyclists versus untrained individuals (aged 18-30 years) found no differences between groups [41] indicating that other mechanisms such as lean body mass may need to be investigated [42].…”
Section: Discussionmentioning
confidence: 95%
“…Evidence examining the acute and chronic effects of exercise on appetite, energy intake, and appetite-related hormone responses has been reviewed extensively [ 15 , 16 , 17 , 18 , 19 ]. A brief summary of this body of work is presented in the next section to provide a context for understanding the modulating effects of adiposity, sex, and habitual physical activity on appetite responses to exercise.…”
Section: Appetite Energy Intake and Appetite-related Hormone Respmentioning
confidence: 99%